Association of carotid artery disease with collateralization and infarct growth in patients with acute middle cerebral artery occlusion - Güney, Resul; Potreck, Arne; Neuberger, Ulf; Schmitt, Niclas; Purrucker, Jan; Möhlenbruch, Markus Alfred; Bendszus, Martin; Seker, Fatih (American journal of neuroradiology, 2024)
BACKGROUND AND PURPOSE: Collaterals are important in large vessel occlusions (LVO), but the role of carotid artery disease (CAD) in this context remains unclear. This study aimed to investigate the impact of CAD on intracranial collateralization and infarct growth after thrombectomy in LVO. - MATERIALS AND METHODS: All patients who underwent thrombectomy due to M1 segment occlusion from 01/2015 to 12/2021 were retrospectively included. Internal carotid artery stenosis according to NASCET was assessed on the affected and nonaffected sides. Collaterals were assessed according to the Tan score. Infarct growth was quantified by comparing ASPECTS on follow-up imaging with baseline ASPECTS. - RESULTS: In total, 709 patients were included, 118 (16.6%) of whom presented with CAD (defined as severe stenosis ≥70% or occlusion ipsilaterally), with 42 cases (5.9%) being contralateral. Good collateralization (Tan 3) was present in 56.5% of the patients with ipsilateral CAD and 69.1% of the patients with contralateral CAD. The ipsilateral stenosis grade was an independent predictor of good collateral supply (adjusted OR: 1.01; NASCET point, 95% CI: 1.00-1.01; P = .009), whereas the contralateral stenosis grade was not (P = .34). Patients with ipsilateral stenosis of ≥70% showed less infarct growth (median ASPECTS decay: 1; IQR: 0-2) compared with patients with 0%-69% stenosis (median: 2; IQR: 1-3) (P = .005). However, baseline ASPECTS was significantly lower in patients with stenosis of 70%-100% (P < .001). The results of a multivariate analysis revealed that increasing ipsilateral stenosis grade (adjusted OR: 1.0; 95% CI: 0.99-1.00; P = .004) and good collateralization (adjusted OR: 0.5; 95% CI: 0.4-0.62; P < .001) were associated with less infarct growth. - CONCLUSIONS: CAD of the ipsilateral ICA is an independent predictor of good collateral supply. Patients with CAD tend to have larger baseline infarct size but less infarct growth.
Gesehen am 10.06.2024